The Effect of Price, Service Quality, and Location on Purchase Decisions at Tan-Panama Coffee Shop in Denpasar - GUNAWAN, I Putu Bayu Arya; SETINI, Made; PRAMANA, Made Surya (PT Keberlanjutan Strategis Indonesia, 2024)
The industry that has the potential to provide a direct impact on the creative economy is the food sector. One type of culinary business that is currently very popular with the public is a coffee shop. The purpose of this study was to examine how the influence of the Tan-Panama coffee shop in Denpasar City on consumer purchasing decisions by looking at several factors such as price, location, and service quality. This study uses accidental sampling techniques to test and evaluate the causal relationship between two variables. The Slovin formula is used to determine the sample size, and 100 respondents are included in the sample, by utilizing the (t) and (f) tests and multiple linear regression analysis as data analysis techniques. The findings of the study indicate that in the Tan-Panama coffee shop located in Denpasar City, price, service quality, and place all have a positive and significant impact on the variables influenced, namely the decision to buy. Price, service quality, and location have a positive and significant influence on purchasing decisions.